Pengaruh konversi mesin genset 160 cc berbahan bakar bensin dengan converter kit liquefied petroleum gas terhadap emisi gas buang - Berto Yusuf Nugroho; Ahmad Arby Trihatmojo; Anggit Bayu Sasongko; Yoga Arob Wicaksono (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2023)
Usability of portable generators fueled by petroleum as a substitute for the community's primary source of electrical energy when the main electricity source black out is still the best choice for the community, limited space for good air circulation will make emissions harmful to users or community, innovation is needed to reduce the levels of exhaust emissions produced by saving fuel or converting the fuel used, one of which is by replacing the carburetor in portable generators fuel engine with a converter kit using Liquified Petroleum Gas (LPG). In this study, the lowest use of petroleum fuel was obtained at 36.3 ml/minute or 0.406 liters/hour, consumption of LPG fuel is 0.159 liters/hour, exhaust emission test results obtained at 5.3% CO emissions from petroleum fuel and 125 ppm for HC fuel oil emissions, compared to the results of LPG CO exhaust emission tests. of 0.90% and fuel HC emissions ar LPG of 41 ppm, the use of LPG fuel in Portable Generators with a converter kit has the effect of using more efficient fuel and very low fuel emissions.